2006
DOI: 10.1111/j.1365-3059.2006.01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the response of carrot somaclones to Pythium violae, causal agent of cavity spot

Abstract: Cavity spot is a major disease of carrots, causing cavities on the surface of the root. Available commercial varieties show a range of susceptibility but no significant resistance. Seed progeny from 46 tissue culture-derived carrot ( Daucus carota ) somaclones were screened for viability, then 19 selected somaclone families were sown under glasshouse conditions, along with commercial cultivars (Bertan, Nandor, Bolero and Vita Longa) as controls. Mature roots were exposed to Pythium violae in a cavity spot bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Systems subject to instability and disorganised growth demonstrated that cellular organization is a critical feature and that somaclonal variation is related to disorganised growth (Karp 1994;Sivanesan 2007). Generally, the more the organizational structure of the plant is broken down, the greater the chance of mutations occurring (Araújo et al 2001;Cooper et al 2006). Although the direct formation of plant structures from cultured plant tissue, without any intermediate callus phase, minimizes the chance of instability, the stabilizing influence of the meristem is usually lost when plants are grown in culture (Karp 1994).…”
Section: In Vitro Propagation Methods Usedmentioning
confidence: 97%
“…Systems subject to instability and disorganised growth demonstrated that cellular organization is a critical feature and that somaclonal variation is related to disorganised growth (Karp 1994;Sivanesan 2007). Generally, the more the organizational structure of the plant is broken down, the greater the chance of mutations occurring (Araújo et al 2001;Cooper et al 2006). Although the direct formation of plant structures from cultured plant tissue, without any intermediate callus phase, minimizes the chance of instability, the stabilizing influence of the meristem is usually lost when plants are grown in culture (Karp 1994).…”
Section: In Vitro Propagation Methods Usedmentioning
confidence: 97%
“…Induced mutagenesis (chemical or physical) (Fuller et al 2006), somaclonal variation (Cooper et al 2006) and more recently insertional mutagenesis (Xu et al 2006) are commonly applied to generate plant lines with enhanced stress resistance. Assessment of disease resistance or stress tolerance in breeding programs relies largely on visual scoring by experts, which is time-consuming and can generate bias between different experts and experimental repeats (Chaerle and Van Der Straeten 2001;Nilsson 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we carried out the propagation of S. bolanthoides via indirect shoot organogenesis. When unorganized cell mass growth occurs in culture, somaclonal variation may occur in these cells, and plants regenerated from the callus can be genetically different from the donor plant [37][38][39][40]. In this study, the callus stage was not prolonged, and this type of callus stage duration in culture could provide genetic stability of regenerated plants of S. bolanthoides.…”
Section: Discussionmentioning
confidence: 96%